Rule of law approaches to countering transnational organized crime in Africa: going beyond criminal justice - Kelly, Catherine Lena (Trends in organized crime, 2023)
Some African state responses to transnational organized crime (TOC) are criticized for being overly focused on the use of force by military and law enforcement. Policy approaches that promote using criminal law to deter TOC have helped to shift focus away from the kinetic solutions that may otherwise prevail by default. However, empirical studies show that TOC is enabled by a range of development and governance issues that go beyond the criminal justice domain. Synthesizing recent insights from empirical research on African TOC from academia, think tanks, and policy-oriented international organizations, this article makes the case for a more holistic, people-centered justice and rule of law approach to addressing TOC. Such an approach conceives of rule of law not merely as the process or result of enforcing the law, but as a social and political practice of promoting mutual respect and equality between different actors in the state and society. This people-centered justice and rule of law framework creates space to address various development and governance factors affecting the incidence of TOC, including (i) the availability of alternative livelihoods, (ii) the popular legitimacy of the state and its influence on people’s regard for the laws on paper; and (iii) the prevalence of a balance of powers enabling the oversight of all actors involved in TOC, especially certain state officials who facilitate it. Beyond the conventionally punitive approaches to addressing TOC, African leaders could explore the potential of more inclusive policymaking processes, the combined use of formal and informal justice institutions to address the drivers of crime, and the empowerment of marginalized groups affected by counter-TOC policy decisions made by elites.